Corporate resilience in the face of COVID-19: A proposal measurement index - Ajili Ben Youssef, Wissem; Ben Slimene, Imen; Maliki, Samir; Kertous, Mourad; Khalil, Afef; Nassiri, Abdelhak; Abdelli, Mohammed (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
The paper aims to revisit the business resilience concept in the specific case of the COVID-19 pandemic. We examine firm resilience factors in ten European and Mediterranean countries. Through a cross-sectional study of a sample of 3,722 firms in all industries, we analyze how firms have survived the crisis. By constructing a multidimensional index identifying resilient companies, the paper contributes to the theoretical and empirical literature and defines a methodology that assesses a firm’s resilience to promote a business strategy that encourages the growth process and develops new aptitudes to cope with future crises.